Study on the synergistic preparation of functional soil from multiple coal-based solid wastes - Yanan Liu; Fenglan Han; Fenglan Han; Ning Li; Fuyuan Dong; Changcong An; Wenna Yang; Tingfeng Li (Frontiers in Environmental Science)
Three coal-based solid wastes—fly ash (FA), gasification slag (GS), and coal gangue (CG)—were used to prepare functional soil (FGC) for the ecological restoration of mining areas. It not only solves the problem of shortage of soil resources in the mining area, but also realizes the resourceful use of coal-based solid waste. Investigating the functional soil physicochemical properties and oatgrass growth characteristics revealed the optimal functional soil ratios. Compared with the control (CK) at 30 d, the average pH of the FGC3 (FA: 50wt%; GS: 25wt%; CG: 25wt%) decreased from 9.54 to 8.54, the average organic matter content increased from 2.57% to 7.60%, and the average available potassium and ammonium nitrogen content increased from 38.02 to 2.83 mg⋅kg−1 to 53.46 and 3.21 mg⋅kg−1, respectively. Functional soil bulk density and porosity were superior to Sandy soil somewhere in Ningxia (SL) for GS and CG contents <25wt%. GS and CG significantly improved oatgrass agronomic traits. Compared with CK the average plant height, stem thickness, fresh weight, and dry weight of oatgrass in FGC3 increased from 17.68 cm, 0.99 mm, 0.09 g, and 0.02 g to 27.0 cm, 1.26 mm, 0.24 g, and 0.04 g, respectively. And chlorophyll content was increased by 20.39% compared with CK. This study verified the feasibility of the synergistic preparation of functional soils from three coal-based solid wastes and provides reference for the ecological restoration and large-scale utilization of coal-based solid wastes.